Harnessing Leadership Styles to Enhance the Effectiveness of Secondary Schools Dynamics in the Vhembe District - Thivhavhudzi Muriel Badugela (E-Journal of Humanities, Arts and Social Sciences)
The study aimed to explore the relationship between leadership styles and their effectiveness in enhancing the culture of secondary schools in the Vhembe District, South Africa. The study aimed to identify how different leadership approaches impact educator performance, learner achievement, and overall school dynamics. It also sought to provide recommendations for fostering leadership practices that positively influence these domains. A qualitative research approach was used, using purposive sampling to select 20 participants with substantial experience and knowledge of leadership dynamics within secondary schools in the Vhembe East District. The study collected in-depth insights into the various leadership styles practised and their effects on the school environment through interviews and observations. Key findings revealed a variety of leadership styles, from democratic to authoritarian, and their differing impacts on educators and learners. While collaborative and culturally responsive leadership practices enhanced school culture and performance, inconsistent or overly authoritative leadership led to challenges such as low educator morale and poor learner outcomes. The power and influence theory and Leadership trait theory provided a framework for understanding the dynamics of power and the traits that contribute to effective leadership. The study indicated that enhancing collaborative leadership, promoting culturally responsive practices, and maintaining consistency in leadership approaches are crucial to improving leadership quality in secondary schools. These findings contribute to the scholarship by offering practical insights that can guide the development of leadership training programs and inform policy-making in educational leadership, ultimately aiming to cultivate positive and supportive school dynamics.